Role of LRP1 in the pathogenesis of Alzheimer’s disease: evidence from clinical and preclinical studies - Shinohara, Mitsuru (J Lipid Res, 2017)
Among the LDL receptor (LDLR) family members, the roles of LDLR-related protein (LRP)1 in the pathogenesis of Alzheimer’s disease (AD), especially late-onset AD, have been the most studied by genetic, neuropathological, and biomarker analyses (clinical studies) or cellular and animal model systems (preclinical studies) over the last 25 years. Although there are some conflicting reports, accumulating evidence from preclinical studies indicates that LRP1 not only regulates the metabolism of amyloid-β peptides (Aβs) in the brain and periphery, but also maintains brain homeostasis, impairment of which likely contributes to AD development in Aβ-independent manners. Several preclinical studies have also demonstrated an involvement of LRP1 in regulating the pathogenic role of apoE, whose gene is the strongest genetic risk factor for AD. Nonetheless, evidence from clinical studies is not sufficient to conclude how LRP1 contributes to AD development. Thus, despite very promising results from preclinical studies, the role of LRP1 in AD pathogenesis remains to be further clarified. In this review, we discuss the potential mechanisms underlying how LRP1 affects AD pathogenesis through Aβ-dependent and -independent pathways by reviewing both clinical and preclinical studies. We also discuss potential therapeutic strategies for AD by targeting LRP1.